ANALISIS SISTEM DU PONT UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN (Studi pada PT Astra International Tbk Periode 2012-2016) - Cahyaningsih, Rindang (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study aims to determine and analyze the financial performance of PT Astra International Tbk and subsidiaries during the period 2012-2016 using Du Pont System analysis. Du Pont Systems Analysis is an analysis system intended to show net profit margin (NPM), total assets turnover (TATO), and return on investment (ROI) interact to determine the return on equity (ROE). The type of this research is descriptive research with quantitative approach. Sources of data used are secondary data in the form of corporate financial statements, especially balance sheet and income statement. The results showed that the value of NPM, TATO, and ROI fluctuated during the period 20122016. The fluctuation of the value is not so prominent that it shows that PT Astra International Tbk and its subsidiaries has a good financial performance. This shows that the company is able to make the company's expense to generate sales, manage all assets owned to generate sales, and able to generate the return in the form of net profit on assets invested.Keywords: Financial Performance, Net Profit Margin (NPM), Total Assets Turnover (TATO), Return On Investment (ROI), Return On Equity (ROE).